Development of E-LKPD PjBL With the Insertion of Tri Hita Karana to Improve the Activeness and Learning Outcomes of Class III Elementary School Students - Ni Luh Made Sriariani; I Wayan Kertih; I Wayan Widiana (MASI Mandiri Edukasi, 2026)
The e-LPKD PjBL model with Tri Hita Karana (THK) insertion has not been developed, and student learning outcomes and learning activities are deficient. The purpose is: produce e-LKPD, determine the validity and practicality of the media, and explain the effectiveness of E-LKPD PjBL with THK NInsertion in Improving the Activeness and Learning Outcomes of Science Students. The data collection method is in the form of questionnaires and tests. The type of development research is with the ADDIE model. The study focuses on E-LKPD, with 20 students from grade III A, 22 from grade III B, and four teachers. The data analysis technique uses percentages, prerequisite analysis tests, and hypothesis tests. The results of the study are as follows: (1) E-LKPD is accessed in the form of a link, (2) the results of media validity are 94.38%, material validity is 93.84%, very valid, (3) the results of the practicality percentage are 89.99%, very practical. (4) The results of the effectiveness test obtained Pillai's Trace, Wilks'Lambda, Hotelling's Trace, and Roy's Largest Root values each have a statistical value of F = 83.776 and a significant figure of 0.001, this value is smaller than the significance level of 0.05 (p < 0.05). So, it can be concluded that there is an influence of learning activity and learning outcomes together between students who study with E-LKPD PjBL with THK insertion and without using e-LKPD. The implication for basic education is that it can implement THK with the Pjbl model.